(Uveitis - glaucoma - hyphema syndrome: Clinical case): Síndrome de uveitis - glaucoma - hifema: Caso clínico - Mamani Maquera, Diego José (2023)
Introduction: Uveitis-glaucoma-hyphema syndrome (UGH) is a rare complication of cataract surgery, due to mechanical chafing exerted by an intraocular lens (IOL) on the iris. Clinical case: We present the case of a 64-year-old man with a history of cataract surgery, who presented decreased visual acuity and pain in the right eye. The ophthalmological examination revealed signs of anterior uveitis, elevated intraocular pressure (IOP), microhyphema, and a single-piece foldable IOL in the sulcus that caused a mechanical chafing with the posterior face of the iris. The medical treatment was insufficient, for this reason a folding simple-piece IOL explant surgery was performed and replaced by a three-piece IOL. Postoperative evolution was favorable. Conclusion: We should suspect this complication in patients with a history of cataract surgery, especially in cases in which the IOL is in single-piece and has been implanted outside the capsular bag.